Exploring the Detection of Undeclared Sibutramine in Botanical Weight Loss Products, Black Slim - Sadeghi, Sajjad (International Journal of Pharmaceutical & Biological Archive, 2024)
Background: Currently, a significant number of individuals rely on herbal medicines for their healthcare requirements despite the lack of screening for efficacy and safety in traditional drugs. Regrettably, undeclared active pharmaceutical ingredients (APIs) have been found in traditional medicines that claim to be natural. This study aimed to identify undeclared APIs in weight loss herbal supplements obtained from an online herbal shop in Iran. Materials and Methods: A packet of herbal supplements consisting of 30 capsules was acquired from an online herbal store in Iran. The product is advertised as a weight loss aid. To identify any concealed APIs, a sample of the supplement was analyzed using a gas chromatography/mass spectrometry device. Results: Sibutramine was found in herbal supplements at a concentration of 13.43 ± 0.291 mg/capsule. Conclusion: Although synthetic drug production requires authorization from licensing authorities, the manufacture of herbal supplements in Iran is not regulated. Consequently, guaranteeing the quality and safety of these herbal supplements is vital for patient health.